Selective Immunomodulation of Inflammatory Pathways in Keratinocytes by the Janus Kinase (JAK) Inhibitor Tofacitinib: Implications for the Employment of JAK-Targeting Drugs in Psoriasis - Martina Morelli; Claudia Scarponi; Laura Mercurio; Francesco Facchiano; Sabatino Pallotta; Stefania Madonna; Giampiero Girolomoni; Cristina Albanesi (Journal of Immunology Research)
IFN-γ and IL-22 are deeply involved in the pathogenesis of psoriasis, as they boost the expression of inflammatory genes and alter proliferative and differentiative programs in keratinocytes. The JAK1/JAK2/STAT1 and JAK1/TYK2/STAT3 pathways triggered by IFN-γ and IL-22, respectively, are aberrantly activated in psoriasis, as highlighted by the peculiar STAT1 and STAT3 signatures in psoriatic skin lesions. To limit the detrimental consequences of IFN-γ and IL-22 excessive stimulation, psoriatic keratinocytes activate suppressor of cytokine signaling (SOCS)1 and SOCS3, which in turn dampen molecular signaling by inhibiting JAK1 and JAK2. Thus, JAK targeting appears to be a reasonable strategy to treat psoriasis. Tofacitinib is an inhibitor of JAK proteins, which, similarly to SOCS, impedes JAK phosphorylation. In this study, we evaluated the immunomodulatory effects of tofacitinib on epidermal keratinocytes in in vitro and in vivo models of psoriasis. We demonstrated the selectivity of tofacitinib inhibitory action on IFN-γ and IL-22, but not on TNF-γ or IL-17 proinflammatory signaling, with suppressed expression of IFN-γ-dependent inflammatory genes, and restoration of normal proliferative and differentiative programs altered by IL-22 in psoriatic keratinocyte cultures. Tofacitinib also potently reduced the psoriasiform phenotype in the imiquimod-induced murine model of psoriasis. Finally, we found that tofacitinib mimics SOCS1 or SOCS3 activities, as it impaired the same molecular pathways in IFN-γ or IL-22-activated keratinocytes.